2022
DOI: 10.1128/spectrum.00609-22
|View full text |Cite
|
Sign up to set email alerts
|

Boosting with Multiple Doses of mRNA Vaccine after Priming with Two Doses of Protein Subunit Vaccine MVC-COV1901 Elicited Robust Humoral and Cellular Immune Responses against Emerging SARS-CoV-2 Variants

Abstract: Vaccination is the most important strategy to combat the COVID-19 outbreak; however, it remains to be determined whether heterologous prime-boost regimens could induce equal or even stronger immune responses against SARS-CoV-2. Here, we showed that boosting the additional doses of mRNA-1273 (Mod) priming with two doses of MVC-COV1901 (MVC) (2× MVC/Mod) improved humoral and cellular immunity compared to two doses of AZD1222 (2× AZ) or MVC (2× MVC) against SARS-CoV-2 variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The characteristics of the included studies are summarized in Table 1 . They were conducted one in each of the following countries: India ( 21 ), Singapore ( 20 ), Malaysia ( 16 ), Israel ( 13 ), UK ( 19 ), Qatar ( 12 ), Brazil ( 18 ), Abu Dhabi ( 17 ), Turkey ( 15 ), and China ( 14 ). The proportion of the female ranged from 7.1 to 78.5% and the median age ranged from 33 to 56 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the included studies are summarized in Table 1 . They were conducted one in each of the following countries: India ( 21 ), Singapore ( 20 ), Malaysia ( 16 ), Israel ( 13 ), UK ( 19 ), Qatar ( 12 ), Brazil ( 18 ), Abu Dhabi ( 17 ), Turkey ( 15 ), and China ( 14 ). The proportion of the female ranged from 7.1 to 78.5% and the median age ranged from 33 to 56 years.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies included patients who received an mRNA (BNT162b2 or mRNA-1273) booster after the standard two-dose mRNA full vaccination ( 12 , 13 , 16 , 19 , 20 ); five studies included patients who received an inactivated booster vaccine after two-dose inactivated full vaccination ( 15 17 , 20 , 21 ); three studies included patients who received an mRNA booster vaccine after two-dose inactivated full vaccination ( 14 16 ); and one study included patients who received an mRNA-1273 booster vaccine after two-dose MVC-COV1901 vaccination ( 14 ). The qualitative analysis included the following studies: two studies reported the seroconversion rates of antibodies against different SAS-CoV-2 fragments ( 15 , 21 ), three studies reported antibody titers ( 14 , 17 , 21 ), and two studies reported cell-mediated immune response after booster vaccination ( 14 , 21 ). The meta-analysis included the following studies: six studies reported laboratory-confirmed SARS-CoV-2 infection ( 12 , 13 , 16 , 18 20 ), three studies reported COVID-19-related ICU admission ( 16 , 18 , 20 ), and four studies reported mortality after that booster vaccination ( 12 , 13 , 16 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the current study again validate the applicability and immunogenicity of a heterologous, adenovirus vector vaccine prime, and mRNA vaccine boost regimen and proves that these two SARS-CoV-2 vaccines work together effectively. The mRNA booster not only elicits strong humoral and cellular immune response in the adenovirus vaccine primed vaccinees but also the inactive vaccine, CoronaVac (Sinovac) or protein subunit vaccine, MVC-COV1901 (MVC) primed vaccines [ 37 , 38 ]. These results support the value and use of mRNA vaccines as the booster to enhance post-primary immune response regardless of prior vaccine platforms.…”
Section: Discussionmentioning
confidence: 99%